If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 87b + 34c = 0 Solving 4a + 87b + 34c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-87b' to each side of the equation. 4a + 87b + -87b + 34c = 0 + -87b Combine like terms: 87b + -87b = 0 4a + 0 + 34c = 0 + -87b 4a + 34c = 0 + -87b Remove the zero: 4a + 34c = -87b Add '-34c' to each side of the equation. 4a + 34c + -34c = -87b + -34c Combine like terms: 34c + -34c = 0 4a + 0 = -87b + -34c 4a = -87b + -34c Divide each side by '4'. a = -21.75b + -8.5c Simplifying a = -21.75b + -8.5c
| 30-8b=-2(1+8b) | | 15x+27=19-31x+8 | | (2/5)a=0 | | 3/4x=110 | | 2x+10=x+8+10 | | Logb=xloga | | (x-97)(x-3)=0 | | x^3-30x+3=0 | | 5a+7b=57 | | 5d-7=13 | | 72.1y= | | 4/9-(7/9-2/9) | | 1/5×10.5 | | 1/7×10.5 | | a^3-6b^2+59c=6 | | 21x^2-12x=-1 | | f(x+7)=x^2+8x+45 | | 9+6x=36 | | 6+5x=456 | | 2senx(cos^2x)-senx=0 | | 2cos^2-5cosx+2=0 | | 3senx+cosx-3=o | | x+2y=123 | | 3senx+cosx-3=0 | | 6(4-x)+55=5(2+3x) | | 26x^2-130x-104=0 | | 5-3x+1=-3 | | x/10-3=7 | | 153.48=2.26w+15.68 | | logy=1.9 | | 5-3x+1=4x-3 | | 19.5=2.26w+15.86 |